2021
DOI: 10.1186/s12931-021-01796-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic respiratory disease and survival outcomes after extracorporeal membrane oxygenation

Abstract: Background Quality of life following extracorporeal membrane oxygenation (ECMO) therapy is an important health issue. We aimed to describe the characteristics of patients who developed chronic respiratory disease (CRD) following ECMO therapy, and investigate the association between newly diagnosed post-ECMO CRDs and 5-year all-cause mortality among ECMO survivors. Methods We analyzed data from the National Health Insurance Service in South Korea. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…31 These patients could continue to have additional radiological testing and further radiation exposure postdischarge in the outpatient setting, adding to their annual and lifetime radiation burden. 32 Indeed, efforts to minimize the CED accrued during the ECMO run and the entire hospital stay could help limit the total lifetime radiation exposure. Unfortunately, despite earnest efforts at our center to limit radiation exposure to as low as reasonably achievable, a select subset was exposed to inordinate doses.…”
Section: Discussionmentioning
confidence: 99%
“…31 These patients could continue to have additional radiological testing and further radiation exposure postdischarge in the outpatient setting, adding to their annual and lifetime radiation burden. 32 Indeed, efforts to minimize the CED accrued during the ECMO run and the entire hospital stay could help limit the total lifetime radiation exposure. Unfortunately, despite earnest efforts at our center to limit radiation exposure to as low as reasonably achievable, a select subset was exposed to inordinate doses.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that chronic respiratory disease-related death is a substantial issue in Asian countries [21], the severe pattern of chronic respiratory diseases such as respiratory disability might affect poorer survival outcomes among South Korean ARDS survivors. In addition, we recently reported that newly developed chronic respiratory diseases were associated with higher 5-year mortality among survivors of ECMO therapy due to respiratory failure or ARDS [22]; thus, ARDS survivors who have a new respiratory disability might also be a high-risk group that needs special attention during healthcare utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, ECMO is widely used in the intensive care unit (ICU). Timely and correct application of ECMO can effectively improve the survival rate of severe patients and even improve the prognosis ( Oh et al., 2021 ; Kochanek et al., 2022 ). However, the infection rate of severe patients should not be underestimated.…”
Section: Introductionmentioning
confidence: 99%